Parents' color-conscious racial socialization and adolescents' racial attitudes: the moderating role of parental psychological control - Agalar, Afra; Laible, Deborah June; Carlo, Gustavo; Liew, Jeffrey (Frontiers in Developmental Psychology, 2024)
Researchers who focus on White U.S. parents' color-conscious socialization practices have predominantly examined the extent, nature, and frequency of conversations about race. However, studies linking such socialization practices to children's racial attitudes are limited to mostly young children and have produced mixed results. The present two-wave longitudinal study examined the relationship between White U.S. parents' color-conscious racial socialization for African Americans and adolescents' racial attitudes, and explored how parental psychological control might moderate this relationship. Participants included 412 White U.S. adolescents (42% girls; Mage = 15.63 years, SD = 1.24) and their primary caregivers (52% mothers). They completed online questionnaires, with parents reporting on their color-conscious racial socialization at Time 1, and adolescents providing measures of their perception of parents' psychological control at Time 1, color-blind attitudes, and racial prejudice at both time points, approximately 16 months apart. Our findings revealed that parents' color-conscious racial socialization for African Americans was negatively associated with adolescents' negative racial attitudes. Additionally, parental psychological control moderated this relation: the negative association was evident only when parents exhibited low or average levels of psychological control. This study highlights the crucial role parents play in shaping their adolescents' racial attitudes and underscores the necessity of an autonomy-supportive environment to enhance the success of parents' color-conscious socialization practices. Understanding these dynamics is essential for developing effective interventions to reduce racial biases and foster inclusive attitudes among adolescents.